Complications of General Anesthesia in Older Patients (The Insight, 2023)
Introduction: General anesthesia is a crucial and widely employed anesthetic procedure utilized in various surgical interventions. Without general anesthesia, many of these surgeries, which are often lifesaving or life-altering, would be impracticable. Nonetheless, it's essential to recognize that all medical procedures carry inherent risks, even when administered by skilled professionals. Aim of the study: This study aimed to assess the complications of general anesthesia in older patients. Methods and materials: This prospective observational study was conducted at the Department of Anaesthesiology, Dhaka National Medical Institute Hospital, Dhaka, Bangladesh from December 2022 to September 2023. The study included 43 elderly surgical patients under general anesthesia. Sampling was purposive, and data were collected using a pre-designed questionnaire and analyzed with MS Office tools. Results: Postoperative complications were quite common, with pain at the operative site (81%), dry mouth or increased thirst (78%), and somnolence (69%) being the most prevalent. Additionally, hoarseness (43%), headache (39%), transfusion requirements (35%), and nausea-vomiting (33%) were notable. Some patients experienced muscle weakness and pain, altered consciousness, urination problems, sensations of cold/chills, and pneumonia. Conclusion: The most prevalent postoperative complications for older surgical patients who have undergone general anesthesia are pain at the surgical site, dry mouth, increased thirst, and somnolence. Physicians should also be prepared to address potential complications such as hoarseness, headache, increased transfusion needs, and nausea and vomiting in these patients.
Keywords: Older patients; Complications; General anesthesia; Dry mouth; Increased thirst; Somnolence